Neuro-Immune Regulation in Inflammation and Airway Remodeling of Allergic Asthma - Zhang, Ning; Xu, Jing; Jiang, Congshan; Lu, Shemin (Frontiers in Immunology, 2022)
Allergic asthma is a common chronic inflammation of the airways and causes airway remodeling eventually. For a long time, people have been focusing on the immunological mechanism of asthma. However, in recent years, the role of neuro-regulation in the occurrence of asthma has gradually attracted people's attention. In this review, we firstly describe neuro-immune regulation in inflammation of allergic asthma from two aspects: innate immunity and adaptive immunity. Secondly, we introduce neuro-immune regulation in airway remodeling of asthma. Finally, we prospect the role of pulmonary neuroendocrine cells in the development of asthma. In general, the amount of researches is limited. Further researches on the neural regulation during the occurrence of asthma will help us clarify the mechanism of asthma more comprehensively and find more effective ways to prevent and control asthma.